IDENTIFIKASI DAN PENGENDALIAN OIL LOSS di PT. SMART TBK SURABAYA - , INTAN NANDA HELI PUTRI, Ir. Ag. Suryandono, M. APP. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Sinar Mas Agro Resources and Technology Tbk Surabaya is one of the oil refinery plant owned by PT. SMART Tbk is located in the city of Surabaya. PT. SMART Tbk is a publicly traded company palm-based consumer products. The company produces palm cooking oil, margarine and shortening, as well as byproducts such as PFAD. The raw materials used are manufactured cpko whereas CPO exports to scale. Production process starting from raw material pedistribusian, purification process (Refinery), the process of separation (Fractionatio), until the storage process. In practice, the production process is always characterized by an imbalance of the number of incoming raw materials / finished products manufactured by the number. Imbalance quantity is often called the Oil Losses. This study uses the concept of material balance (Material Balances) to identify the process. Data used include primary data in the form of direct interviews with the company, the data Losses owned companies, as well as secondary data from the literature that support the research. Collected data were processed using a causal diagram, and will be evaluated using analysis table problem. Results obtained from the study is Oil Loss in the industry divided into two categories namely Loss in Process contained in the purification process (Refinery) precisely on the bleaching process and the Oil Stock Loss Loss that occurs outside the refining process such as the distribution of raw materials, the process of separation ( fractisonation), the process of filling and packaging, and storage processes. Of a causal diagram that has been made, it appears that the factors that affect the Oil Loss in Process include additional levels of Bleaching Earth, water content (moisture), levels of impurities, and Uncounted Loss. While the factors that influence the Stock Loss divided into two types namely unintentional mistakes (unforced errors) such as human error, mechanical failure, and the oil tank leaks and deliberate mistakes (Forced Error) as oil theft. The most important control that needs to be done is to develop human resources, with increasing human resources will improve the quality of the process. Methods, machinery and equipment will be refurbished, the environment will kerjapun well controlled as well as issues such as impact damage Oil Loss will be identified and the percentage of the losses can be reduced.